PENGARUH ISI KANDUNGAN SURAT AN-NAHL AYAT 68-69 DALAM MENINGKATKAN KREATIVITAS SISWA DI SMPN 3 CIBINONG - Raja, Muhammad Divo; Ikhtiono, Gunawan; Sobari, Ahmad (Inspiratif Pendidikan, 2021)
This study aims to determine whether there is a significant influence between the contents of the surah An-Nahl verses 68-69 in increasing student learning creativity at SMP N 3 Cibinong in the 2020-2021 academic year. This study also uses two variables, namely the contents of the surah An-Nahl verses 68-69 as the independent variable and student creativity as the dependent variable. The sample used in this study were 40 students of class VII-5 who had a pretty good creativity in learning, then class VIII-2, which amounted to 40 students, where this class was considered to be less enthusiastic in participating in teaching and learning activities and class. IX-5, amounting to 40 students who have the intelligence to think in solving problems. The technique used by researchers is random sampling. The results of this study indicate that there is no positive and significant effect between the variable content of the An-Nahl verse 68-69 surah and the variable of learning creativity calculated by Pearson Correlation. Based on the research results, it can be said that there is not a sufficient relation between the variable content of the content of the surah An-Nahl verses 68-69 and the variable of student learning creativity at SMP N 3 Cibinong. This means that there is no influence from the contents of the letter An-Nahl verses 68-69 in increasing student creativity.